Peningkatan SDM Wanita Hindu Melalui Pengabdian Masyarakat (Tematik ) Pemberdayaan Perempuan Anti Korupsi - Widiantana, I Kadek; Sentana, Gek Diah Desi; Perbowosari , Heny (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
Corruption can be found in all civilizations. Corruption can appear in various forms and has a wide impact on society. Community Service (Thematic) Women's Empowerment Against Corruption is one of the efforts to improve the quality of human resources, especially Hindu women, in terms of preventing acts of corruption. Implementation of Community Service (Thematic) Women's Empowerment Against Corruption using training methods. Community Service as one part of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education comprising Education, Research and Community Service) to provide knowledge and skills to Hindu women. Through service activities, Hindu women are expected to have the knowledge, understanding and skills in anti-corruption measures and the empowerment of Banten (offerings) as a form of community self-reliance movement, especially Hindu women, with the hope that women can take a big role in anticipating the emergence of corruption activities. Keywords: anti-corruption, swadesi